44 Can the principles of aortic root surgery in adults be safely applied to children. (7th October 2015) - Ayoubi, A; McGuinness, J; Nolke, L; Redmond, M
Abstract : Objective: Surgical algorithms for aortic root disease are established in adults. The root of children needs to have a potential for somatic growth, therefore a spectrum of techniques can be used to reconstruct the root. This study reviews a national experience in 50 consecutive paediatric patients requiring aortic root repair, and evaluates the efficacy of our treatment algorithm in this age group. Methods: All aortic root procedures at our institution from 2001–2014 were reviewed. Follow-up was 100% complete. Patients undergoing aortic valve repair only (n = 7) or Ross/Konno procedures (n = 5) were excluded. Results: There were 27 male patients. Mean age at surgery was 14.5 years (range: 4 weeks-18 years); mean weight was 46.1 kg (range: 3.5–105 kg). The predominant pathology was mixed disease of aortic stenosis (AS) / aortic incompetence (AI) in 28 /50, (AI) in 13/50 and (AS) in 1 /50. Aortic root dilatation (6 Marfan's + 2 Loeys-Dietz syndrome) was the dominant pathology in 8/50 patients. 30/50 patients underwent a Ross procedure; 12/50 patients underwent aortic root replacement (ARR) with aortic homograft/biocomposite graft; 8/50 patients underwent David valve-sparing aortic root replacement (VSARR). There was 1 perioperative death (2%) with a 5 year actuarial survival of 98%. Mean follow up was 3.96 years (range: 0.1–11.6 years). There were no late mortalities. Re-intervention was required in 4/50 (8%); 1 Ross patient required (VSARR) for autograft dilatation, 2 required redo (ARR) with a composite graft for acute homograft failure, and 1 (VSARR) patient required mechanical AVR for AI. Conclusion: Aortic root surgery in children can be accomplished with low rates of early-mid term re-intervention and mortality. Our experience confirms the applicability of adult treatment principles, and highlights the need for versatility in surgical technique in children.